PERAMALAN HARGA TELUR AYAM DENGAN METODE EXPONENSIAL SMOOTHING WINTERS DI KABUPATEN SUKOHARJO - Nugraheni, Ria Pertiwi; Rimawati, Elistya; Vulandari, Retno Tri (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2025)
Forecasting is the process of estimating future price trends based on historical price data. The price of rice and eggs in Sukoharjo Regency, based on data from Dinas Perdagangan, Koperasi, dan UMKM Sukoharjo from January 2016 to August 2019, has shown frequent fluctuations. To address this issue, an accurate forecasting method is needed to help predict future prices of rice and eggs, minimize price volatility, and assist in decision-making for both consumers and stakeholders. This study applies the Exponential Smoothing Winters method, a seasonal forecasting technique that incorporates level, trend, and seasonal components. A price prediction application was developed using the VB.NET programming language and SQL Server database. The application generates predictive calculations for rice and egg prices, complemented by graphical displays and report outputs. The results of the study show Mean Absolute Percentage Error (MAPE) values of 14.57% for broiler eggs and 6.74% for native chicken eggs. These results indicate that the method provides a relatively high level of accuracy.